ΠΑΡΟΥΣΙΑΣΗ ΝΕΩΝ ΒΙΒΛΙΩΝ - Ευαγγελάτου-Νοταρά, Φλιορεντία; Δελλής, Ι. Γ.; Μπόμπου-Σταμάτη, Βασιλική; Μπίρταχας, Στάθης; Τσελέντη, Νίκη; Μέντζου-Μεϊμάρη, Κωνσταντίνα; Μανιάτη-Κοκκίνη, Τριανταφυλλίτσα; Κουταβά-Δεληβοριά, Βαρβάρα (Eoa kai Esperia, 2003)
Twenty two book presentations and reviewes.